Development of Learning Media Augmented Reality Nervous System (ARSaf) to Improve Student Understanding - Rohmah, Sifa Wahdatun; Anggraito, Yustinus Ulung (FMIPA UNNES, 2021)
Learning practices in the midst of the Covid-19 pandemic do not allow face-to-face meetings at schools. In order to optimize the learning process, it is necessary to have appropriate learning supports and allow students to learn from home. The nervous system is a material that is difficult for students to understand because of its complex and abstract. Augmented Reality (AR)-based learning media can involve students in the learning process and help improve visualization skills. The purpose of this study was to analyze the feasibility of Augmented Reality Nervous System (ARSaf) learning media to improve students' understanding. This study uses a 3-D model (define, design, and develop) which is modified from the 4-D model by Thiagarajan, Semmel, and Sammel (1974) covering the define, design, develop, and disseminate stages. ARSaf learning media validation was carried out to validate the media and material aspects. Validation was carried out by media experts, materials experts, and biology teachers using a modified questionnaire from the 2014 BSNP and the book